Group analysis of motion equation of charged particle placed in crossed fields - Yeliseyev, Yu.N. (Вопросы атомной науки и техники, 2019)
The transformation of motion equation of a charged particle placed in crossed longitudinal magnetic field and radial electric one is considered under transition from the laboratory frame of reference to a uniformly rotating coor-dinate system. It is shown that the transformation of equation in a plane transversal to the magnetic field admits a group. Using the method of group analysis, the transformation invariant and canonical variables are found.